Prolonged adaptability of highly qualified athletes to training stresses, studied by longitudinal metabolomic analysis of biofluids - Viryus E.D. ,; Dikunets M.A. ,; Fedotova E.V. ,; Dudko G.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the feasibility of longitudinal metabolome analysis of biological samples from elite athletes to identify previously unknown and highly sensitive metabolic processes associated with long-term adaptation to intense training. Methods and structure of the study. To identify metabolic pathways associated with long-term adaptation to training in elite athletes, a computerized search and analysis of relevant scientific publications describing the capabilities of longitudinal metabolomic analysis of biological samples was performed. The search was conducted in the electronic scientific citation databases PubMed, Scopus and Web of Science to identify relevant studies. Results and conclusions. Careful planning of the pre-analytical phase (including selection of study participants, definition of the analyzed sample, choice of methodology and approach to profiling) is the key to successful longitudinal metabolomic analysis of biological fluids in professional athletes involved in a long-term training cycle. Using such opportunities allows identifying significant shifts in the functioning of the physiological systems of the body of the trainee (endocrine, cardiovascular, oxygen transport system, energy metabolism at the cellular level), which are reflected in the metabolomic profile of the studied biological fluid. Systematic multi-month training forms a specific phenotype of a highly qualified athlete, determined by his individual ability to adapt and having a unique metabolomic expression. Longitudinal metabolomic analysis of biological fluids provides information necessary for an in-depth study of the mechanisms of long-term adaptive changes occurring in the body of professional athletes.